2011
DOI: 10.1186/1475-2875-10-76
|View full text |Cite
|
Sign up to set email alerts
|

Malaria diagnostic testing and treatment practices in three different Plasmodium falciparum transmission settings in Tanzania: before and after a government policy change

Abstract: BackgroundPatterns of decreasing malaria transmission intensity make presumptive treatment of malaria an unjustifiable approach in many African settings. The controlled use of anti-malarials after laboratory confirmed diagnosis is preferable in low endemic areas. Diagnosis may be facilitated by malaria rapid diagnostic tests (RDTs). In this study, the impact of a government policy change, comprising the provision of RDTs and advice to restrict anti-malarial treatment to RDT-positive individuals, was assessed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 33 publications
3
56
1
Order By: Relevance
“…Even when tests are carried out, findings are accumulating from studies in different countries that show between 35 and 85% of RDT negative patients have been prescribed antimalarials Bisoffi et al, 2009;Chinkhumba et al, 2010;Elmardi et al, 2009;Hamer et al, 2007;Kyabayinze et al, 2010;Reyburn et al, 2007;Skarbinski et al, 2009). By contrast, other studies have found a reduction in overdiagnosis, down to between 4% and 16% RDT negative patients receiving antimalarials after the introduction of RDTs with various supporting interventions (Bastiaens et al, 2011;D'Acremont et al, 2009;Hopkins, 2008;Masanja et al, 2010;Mawili-Mboumba et al, 2009;Msellem et al, 2009;Thiam et al, 2011;Williams et al, 2008). In spite of this mixed evidence over the effect of introducing RDTs, and in the absence of good information about the best way to support their introduction for effective adoption, scale-up of the tests is being promoted (World Health Organisation, 2010), and many countries including Cameroon have included the tests in their Global Fund grant applications (Ministry of Public Health, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…Even when tests are carried out, findings are accumulating from studies in different countries that show between 35 and 85% of RDT negative patients have been prescribed antimalarials Bisoffi et al, 2009;Chinkhumba et al, 2010;Elmardi et al, 2009;Hamer et al, 2007;Kyabayinze et al, 2010;Reyburn et al, 2007;Skarbinski et al, 2009). By contrast, other studies have found a reduction in overdiagnosis, down to between 4% and 16% RDT negative patients receiving antimalarials after the introduction of RDTs with various supporting interventions (Bastiaens et al, 2011;D'Acremont et al, 2009;Hopkins, 2008;Masanja et al, 2010;Mawili-Mboumba et al, 2009;Msellem et al, 2009;Thiam et al, 2011;Williams et al, 2008). In spite of this mixed evidence over the effect of introducing RDTs, and in the absence of good information about the best way to support their introduction for effective adoption, scale-up of the tests is being promoted (World Health Organisation, 2010), and many countries including Cameroon have included the tests in their Global Fund grant applications (Ministry of Public Health, 2009).…”
Section: Introductionmentioning
confidence: 74%
“…With reports of the decline in the incidence of malaria in many African countries (Bouyou-Akotet et al, 2009;Delacollette et al, 2009;Satoguina et al, 2009), it is imperative that parasite confirmation of malaria be scaled up in all age groups. Rapid diagnostic tests (RDTs) are cheap and practical for improving on the diagnosis and treatment of malaria and have been adopted as a public health policy in several African countries (Reyburn et al, 2007;Bisoffi et al, 2009;Bastiaens et al, 2011). The causes of nonmalarial fevers can then be followed up and managed appropriately (Oladipo and Wellington, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from the scientifi c record on the eff ect of diagnostic testing on prescription behaviour is mixed. 204,205 The increased prescription of antibiotics in the setting of a negative rapid diagnostic test fi nding for malaria might lead to improved rational use, or it could just result in overprescription of antibiotics as compensatory behaviour to mollify patients' expectations of treatment. 206 In the health-care delivery system, antibiotic steward ship might be through integrated community case management.…”
Section: Scale-up and Implementationmentioning
confidence: 99%